Combining the new injury severity score with an anatomical polytrauma injury variable predicts mortality better than the new injury severity score and the injury severity score: a retrospective cohort study. Issue 1 (December 2016) - Wong, Ting; Krishnaswamy, Gita; Nadkarni, Nivedita; Nguyen, Hai; Lim, Gek; Bautista, Dianne; Chiu, Ming; Chow, Khuan; Ong, Marcus
Abstract Background Anatomy-based injury severity scores are commonly used with physiological scores for reporting severity of injury in a standardized manner. However, there is lack of consensus on choice of scoring system, with the commonly used injury severity score (ISS) performing poorly for certain sub-groups, eg head-injured patients. We hypothesized that adding a dichotomous variable for polytrauma (yes/no for Abbreviated Injury Scale (AIS) scores of 3 or more in at least two body regions) to the New Injury Severity Score (NISS) would improve the prediction of in-hospital mortality in injured patients, including head-injured patients—a subgroup that has a disproportionately high mortality. Our secondary hypothesis was that the ISS over-estimates the risk of death in polytrauma patients, while the NISS under-estimates it. Methods Univariate and multivariable analysis was performed on retrospective cohort data of blunt injured patients aged 18 and over with an ISS over 9 from the Singapore National Trauma Registry from 2011–2013. Model diagnostics were tested using discrimination (c-statistic) and calibration (Hosmer-Lemeshow goodness-of-fit statistic). All models included age, gender, and comorbidities. Results Our results showed that the polytrauma and NISS model outperformed the other models (polytrauma and ISS, NISS alone or ISS alone) in predicting 30-day and in-hospital mortality. The NISS underestimated the risk of death for patients with polytrauma, while the ISS overestimated the risk of death for these patients. When used together with the NISS and polytrauma, categorical variables for deranged physiology (systolic blood pressure of 90 mmHg or less, GCS of 8 or less) outperformed the traditional 'ISS and RTS (Revised Trauma Score)' model, with a c-statistic of greater than 0.90. This could be useful in cases when the RTS cannot be scored due to missing respiratory rate. Discussion The NISS and polytrauma model is superior to current scores for prediction of 30-day and in-hospital mortality. We propose that this score replace the ISS or NISS in institutions using AIS-based scores. Conclusions Adding polytrauma to the NISS or ISS improves prediction of 30-day mortality. The superiority of the NISS or ISS depends on the proportion of polytrauma and head-injured patients in the study population.